AHL-Lactonase Producing Psychrobacter sp. From Palk Bay Sediment Mitigates Quorum Sensing-Mediated Virulence Production in Gram Negative Bacterial Pathogens - Packiavathy, Issac Abraham Sybiya Vasantha; Kannappan, Arunachalam; Thiyagarajan, Sivaprakasam; Srinivasan, Ramanathan; Jeyapragash, Danaraj; Paul, John Bosco John; Velmurugan, Pazhanivel; Ravi, Arumugam Veera (Frontiers in Microbiology, 2021)
Quorum sensing (QS) is a signalingsignalling mechanism governed by bacteria to converse at inter- and intra-species level through small self-produced chemicals called N-acylhomoserine lactones (AHLs). Through QS, bacteria regulate and organize the virulence factors production including biofilm formation. AHLs can be degraded by an action called quorum quenching (QQ) and hence QQ strategy can effectively be employed to combatontain biofilm associated bacterial pathogenesis. The present study was aimed to identify novel bacterial species with QQ potential. Screening of Palk bay marine sediment bacteria for QQ activity ended up with the identification marine bacterial isolate 28 (MSB-28), which exhibited a profound QQ activity against QS biomarker strain Chromobacterium violaceum 12472. The isolate MSB-28 was identified as Psychrobacter sp. through 16S-rRNA sequencing. Besides, Psychrobacter sp. demonstrated a pronounced activity in controlling the bioﬁlm formation in different bacteria and biofilm associated virulence factors production in P. aeruginosa PAO1. Solvent extraction, heat inactivation and proteinase K treatment assays clearly evident the enzymatic nature of the bioactive lead. Furthermore, AHL’s lactone ring cleavage was confirmed with experiments including ring closure assay and chromatographic analysis, and thus the AHL-lactonase enzyme production in Psychrobacter sp. To conclude, this is the first report stating the AHL-lactonase mediated QQ activity from marine sediment bacteria Psychrobacter sp. Future work deals with the characterization, purification, and mass cultivation of the purified protein will pave the way to assess the feasibility of the identified protein in controlling QS and biofilm mediated multidrug resistant bacterial infections in mono or multi-species conditions.